Collaborative governance and urban food security: Institutional challenges and household determinants in Pekanbaru, Indonesia - Wasiah Sufi; Sujianto Sujianto; Febri Yuliani; Hasim As'ari (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
Urban food security has become a critical developmental challenge, particularly in rapidly urbanizing regions where traditional governance structures struggle to address systemic vulnerabilities. This study aims to examine the institutional challenges and coordination mechanisms of food security governance in Pekanbaru City, while identifying the socio-economic determinants of household food insecurity. Using a convergent parallel mixed-method design, quantitative data from 788 households (SUSENAS 2022) were analyzed through multinomial logistic regression, complemented by a qualitative SWOT analysis involving 18 key stakeholders. Findings reveal that while 77.79% of households are food secure, significant pockets of vulnerability persist. Severe food insecurity is primarily driven by an absence of savings (OR=0.285) and high food expenditure ratios (OR=0.277), while moderate insecurity is strongly linked to poverty status (OR=7.987) and female-headed households (OR=0.320). Institutional analysis identifies strengths in dedicated agencies but highlights critical weaknesses in cross-sector coordination and regulatory frameworks. The study proposes a